Preparation method and application of Mn-doped RuO2 nanosheet catalyst
By adopting water thermal reaction and ion exchange technology in the RUO2 catalyst preparation, the 钌 element is limited to the 2D structure MN (OH) 2 hexagonal nano -tablet template, and the MN doped RUO2 nanosilateral catalyst is prepared to solve the RU atomic The problems of low reunion and low activity have realized the ORR catalytic performance similar to the commercial PT/C catalyst.
Patent Information
- Application Number
- CN202411418576.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-12
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-10-12
AI Technical Summary
During the preparation process of high-temperature calcination, Ru atoms are prone to agglomeration, resulting in a decrease in the number of active sites and a low utilization rate; its intrinsic activity is also far lower than that of commercial Pt/C catalysts, making it difficult to apply to the positive electrode reaction of fuel cell.
The 2D structure MN (OH) 2 hexagonal nanoscope is obtained through the water heat reaction, and the elemental element is limited to the hexagonal nanoplastment template through an ion exchange reaction.
The ORR catalytic activity of the catalyst is improved, the RU atomic reunion is avoided, the active site is increased, the utilization of the precious metal RU atom is improved, and the electronic structure of the catalyst and the adsorption/absorbing ability of the intermediate body is optimized.
Smart Images

Figure CN118919748B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of preparation of positive electrode materials for fuel cells, and in particular to a preparation method and application of a Mn-doped RuO2 nanosheet catalyst. Background Art
[0002] Oxygen reduction reaction (ORR) is a cathode reaction in new energy storage and conversion devices such as fuel cells. However, the complex electron transfer of ORR leads to its slow kinetics, which greatly hinders its application in practical devices. Currently, the most effective ORR electrocatalyst is still platinum (Pt)-based precious metal catalyst, and its high cost limits its large-scale commercial application in devices such as fuel cells.
[0003] In recent years, various metal-based catalysts have been developed for electrochemical devices. Among them, RuO2 noble metal catalysts, as one of the most effective electrocatalysts, are only one-tenth the price of Pt and have attracted widespread attention. Currently, the RuO2 catalysts used are mainly prepared by calcining metal ruthenium salts loaded with carbon as a carrier, or directly by calcining metal ruthenium salts.
[0004] A Chinese patent document with publication number CN105006379A discloses a ruthenium dioxide nanocluster / carbon composite material and a preparation method thereof, wherein a ruthenium precursor solution is prepared, a reducing agent is added to obtain ruthenium nanoclusters dispersed in water, a carbon-based material is dispersed therein to obtain a ruthenium nanocluster / carbon composite material, and the obtained composite material is calcined at a high temperature to obtain a ruthenium dioxide nanocluster / carbon composite material.
[0005] A Chinese patent document with publication number CN115818740A discloses a method for preparing ruthenium dioxide powder, which directly uses ruthenium chloride as a raw material and dissolves it in deionized water, uses H2O2 or NaClO as an oxidant to react, and obtains black RuO2 solid powder through aging, centrifugation, washing, roasting, and grinding.
[0006] There are two main problems with the preparation methods of the above two RuO2 catalysts. First, during the high-temperature calcination process to prepare the RuO2 catalyst, Ru atoms are prone to agglomeration, which reduces the number of active sites and leads to low utilization of Ru atoms. Second, the prepared RuO2 catalyst is difficult to use in catalytic fuel cell cathode reactions because its intrinsic activity is much lower than that of traditional commercial Pt / C catalysts. Summary of the invention
[0007] The first object of the present invention is to provide a method for preparing a Mn-doped RuO2 nanosheet catalyst, wherein the Mn-doped RuO2 nanosheet catalyst prepared by the method has an ORR catalytic performance similar to that of a commercial Pt / C catalyst; the second object is to provide an application of the Mn-doped RuO2 nanosheet catalyst prepared by the above method in the positive electrode of a fuel cell.
[0008] In order to solve the above technical problems, the present invention adopts the following technical solutions:
[0009] In a first aspect, the present invention provides a method for preparing a Mn-doped RuO2 nanosheet catalyst, comprising the following steps:
[0010] 1) Under stirring, hydrazine hydrate is added dropwise to a potassium permanganate aqueous solution to obtain solution A, and then a hydrothermal reaction is performed to obtain a suspension B. The suspension B is centrifuged and vacuum freeze-dried to obtain a precipitate A, i.e., 2D structured Mn(OH)2 hexagonal nanosheets;
[0011] 2) Ultrasonic dispersion of 2D structured Mn(OH)2 hexagonal nanosheets and metal ruthenium salt in a solvent, stirring to cause an ion exchange reaction, to obtain a suspension C, centrifuging, washing, and drying the suspension C to obtain a precipitate B, and calcining the precipitate B to obtain a Mn-doped RuO2 nanosheet catalyst.
[0012] Furthermore, in the step (1), the concentration of the potassium permanganate aqueous solution is 5-10 g / L, the mass ratio of potassium permanganate to hydrazine hydrate is 1:2.5-5; the hydrothermal reaction temperature is 150-200°C, and the hydrothermal reaction time is 12 hours; and the drying is performed by vacuum freeze drying;
[0013] Furthermore, in step (2), the solvent is at least one of water, methanol or ethanol; the metal ruthenium salt is at least one of ruthenium trichloride, ruthenium acetate or carbonyl ruthenium chloride; the ratio of 2D structure Mn(OH)2 hexagonal nanosheets, metal ruthenium salt and solvent is 1g:0.5-2g:0.5-1L; the ion exchange reaction time is 6-24h; and the calcination process is to control the heating rate to 2-10℃ / min and heat to 400-900℃, and keep warm for 2h.
[0014] In a second aspect, the present invention also provides an application of the Mn-doped RuO2 nanosheet catalyst prepared by the above method in the positive electrode of a fuel cell.
[0015] Compared with the prior art, the present invention has the following beneficial effects:
[0016] (1) The technical scheme of the present invention first prepares 2D structured Mn(OH)2 hexagonal nanosheets through a hydrothermal reaction, then confines the ruthenium element to the hexagonal nanosheet template through an ion exchange reaction, and then calcines to obtain a Mn-doped RuO2 nanosheet catalyst. By confining the ruthenium element to the hexagonal nanosheet template, the problem of easy agglomeration of Ru atoms in the traditional method of directly pyrolyzing metal ruthenium salt to prepare RuO2 catalyst is avoided, the active sites are increased, and the ORR catalytic activity of the catalyst is improved.
[0017] (2) The Mn-doped RuO2 nanosheet catalyst prepared by the technical solution of the present invention has a unique hexagonal nanosheet structure, and the smaller hexagonal nanometer size of 300-500nm can avoid the collapse or accumulation of the sheet structure, thereby providing a larger specific surface area; and the smaller hexagonal nanometer size can fully expose the active sites of the precious metal Ru atoms, thereby improving the utilization rate of the precious metal Ru atoms in the catalytic process; and the 2D hexagonal nanosheet structure can provide a good contact interface between the active sites and the electrolyte, thereby promoting the efficiency of electron / ion transmission.
[0018] (3) The technical solution of the present invention realizes the doping of Mn atoms through ion exchange and high-temperature pyrolysis. The doping of Mn atoms can adjust the d-band center of the precious metal Ru atoms, optimize the electronic structure of the RuO2 catalyst and the adsorption / desorption ability of the reaction intermediates on the Ru site, and solve the problem that the intrinsic activity of Ru is much lower than that of the commercial Pt / C catalyst.
[0019] (4) The technical solution of the present invention controls the ion exchange reaction time between 6 and 24 hours, so that the prepared Mn-doped RuO2 nanosheet catalyst maintains the morphological characteristics of hexagonal nanosheets. This method is simple and easy to control, and can quickly and controllably prepare Mn-doped RuO2 nanosheet catalysts, providing an effective synthetic path for the large-scale development and utilization of ORR catalysts.
[0020] (5) The present invention prepares Mn-doped RuO2 nanosheet catalysts for use as fuel cell cathode ORR catalysts, which exhibit excellent performance in the ORR field. In an alkaline environment of 0.1M KOH, its half-wave potential is 0.81-0.84V, which has similar performance to commercial Pt / C catalysts. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 The X-ray powder diffraction pattern (XRD) of 2D-Mn-RuO2 prepared in Example 1;
[0022] Figure 2 Transmission electron microscopy (TEM) image of Mn(OH)2 hexagonal nanosheets prepared in Example 1;
[0023] Figure 3 Transmission electron microscopy (TEM) image of 2D-Mn-RuO2 prepared in Example 1;
[0024] Figure 4 Electrochemical linear sweep voltammetry (LSV) curves of 2D-Mn-RuO2 of Example 1, RuO2 prepared in Comparative Example 1, and commercial Pt / C catalyst;
[0025] Figure 5 This is a transmission electron microscopy (TEM) image of the nanosheets of the RuO2 catalyst prepared in Comparative Example 1;
[0026] Figure 6 is the X-ray powder diffraction pattern (XRD) of the catalyst prepared in Comparative Example 2;
[0027] Figure 7 is the X-ray powder diffraction pattern (XRD) of the catalyst prepared in Comparative Example 3;
[0028] Figure 8 is a transmission electron microscopy (TEM) image of the catalyst prepared in Comparative Example 4; DETAILED DESCRIPTION
[0029] The present invention is further described below by way of examples and drawings, but the protection scope of the present invention is not limited thereto. Example 1
[0030] (1) Under stirring, 10 mL of hydrazine hydrate solution (50 wt%) was added dropwise to 100 mL of 10 g / L potassium permanganate solution to obtain solution A, which was then subjected to a hydrothermal reaction at 150 °C for 12 h to obtain suspension B. The suspension B was centrifuged and vacuum freeze-dried to obtain precipitate A, i.e., 2D structured Mn(OH)2 hexagonal nanosheets;
[0031] (2) 1 g of Mn(OH)2 hexagonal nanosheets and 1 g of ruthenium trichloride were ultrasonically dispersed in 0.5 L of deionized water and stirred for 12 h for ion exchange reaction to obtain suspension C. Suspension C was centrifuged, washed, and dried to obtain precipitate B. Precipitate B was heated to 600 °C at a rate of 5 °C / min and reacted for 2 h to obtain Mn-doped RuO2 nanosheet catalyst, named 2D-Mn-RuO2. Example 2
[0032] (1) Under stirring, 5 mL of hydrazine hydrate solution (50 wt%) was added dropwise to 100 mL of 10 g / L potassium permanganate solution to obtain solution A, which was then subjected to a hydrothermal reaction at 150 °C for 12 h to obtain suspension B. The suspension B was centrifuged and vacuum freeze-dried to obtain precipitate A, i.e., 2D structured Mn(OH)2 hexagonal nanosheets;
[0033] (2) 1 g of Mn(OH)2 hexagonal nanosheets and 1.5 g of ruthenium trichloride were ultrasonically dispersed in 0.7 L of deionized water and stirred for 12 h for ion exchange reaction to obtain suspension C. Suspension C was centrifuged, washed, and dried to obtain precipitate B. Precipitate B was heated to 600 °C at a rate of 5 °C / min and reacted for 2 h to obtain Mn-doped RuO2 nanosheet catalyst, named 2D-Mn-RuO2-2. Example 3
[0034] (1) Under stirring, 5 mL of hydrazine hydrate solution (50 wt%) was added dropwise to 100 mL of 5 g / L potassium permanganate solution to obtain solution A, and then the solution was subjected to hydrothermal reaction at 200 °C for 12 h to obtain suspension B. The suspension B was centrifuged and vacuum freeze-dried to obtain precipitate A, i.e., 2D structured Mn(OH)2 hexagonal nanosheets;
[0035] (2) 1 g of Mn(OH)2 hexagonal nanosheets and 2 g of ruthenium trichloride were ultrasonically dispersed in 1 L of deionized water and stirred for 12 h for ion exchange reaction to obtain suspension C. Suspension C was centrifuged, washed, and dried to obtain precipitate B. Precipitate B was heated to 400 °C at a rate of 2 °C / min and reacted for 2 h to obtain Mn-doped RuO2 nanosheet catalyst, named 2D-Mn-RuO2-3. Example 4
[0036] (1) Under stirring, 2.5 mL of hydrazine hydrate solution (50 wt%) was added dropwise to 100 mL of 5 g / L potassium permanganate solution to obtain solution A, which was then subjected to a hydrothermal reaction at 180 °C for 12 h to obtain suspension B. The suspension B was centrifuged and vacuum freeze-dried to obtain precipitate A, i.e., 2D structured Mn(OH)2 hexagonal nanosheets;
[0037] (2) 1 g of Mn(OH)2 hexagonal nanosheets and 2 g of carbonyl ruthenium chloride were ultrasonically dispersed in 0.5 L of methanol and stirred for 18 h for ion exchange reaction to obtain suspension C. Suspension C was centrifuged, washed, and dried to obtain precipitate B. Precipitate B was heated to 400 °C at a rate of 10 °C / min and reacted for 2 h to obtain Mn-doped RuO2 nanosheet catalyst, named 2D-Mn-RuO2-4. Example 5
[0038] (1) Under stirring, 8 mL of hydrazine hydrate solution (50 wt%) was added dropwise to 100 mL of 10 g / L potassium permanganate solution to obtain solution A, which was then subjected to hydrothermal reaction at 180 °C for 12 h to obtain suspension B. The suspension B was centrifuged and vacuum freeze-dried to obtain precipitate A, i.e., 2D structured Mn(OH)2 hexagonal nanosheets;
[0039] (2) 1 g of Mn(OH)2 hexagonal nanosheets and 2 g of ruthenium acetate were ultrasonically dispersed in 0.5 L of ethanol and stirred for 18 h for ion exchange reaction to obtain suspension C. Suspension C was centrifuged, washed, and dried to obtain precipitate B. Precipitate B was heated to 800 °C at a rate of 4 °C / min and reacted for 2 h to obtain Mn-doped RuO2 nanosheet catalyst, named 2D-Mn-RuO2-5. Example 6
[0040] (1) Under stirring, 8 mL of hydrazine hydrate solution (50 wt%) was added dropwise to 100 mL of 10 g / L potassium permanganate solution to obtain solution A, which was then subjected to a hydrothermal reaction at 150 °C for 12 h to obtain suspension B. The suspension B was centrifuged and vacuum freeze-dried to obtain precipitate A, i.e., 2D structured Mn(OH)2 hexagonal nanosheets;
[0041] (2) 1 g of Mn(OH)2 hexagonal nanosheets and 1 g of ruthenium trichloride were ultrasonically dispersed in 1 L of deionized water and stirred for 6 h for ion exchange reaction to obtain suspension C. The suspension C was centrifuged, washed, and dried to obtain precipitate B. The precipitate B was heated to 800 °C at a rate of 8 °C / min and reacted for 2 h to obtain Mn-doped RuO2 nanosheet catalyst, named 2D-Mn-RuO2-6. Example 7
[0042] (1) Under stirring, 8 mL of hydrazine hydrate solution (50 wt%) was added dropwise to 100 mL of 10 g / L potassium permanganate solution to obtain solution A, which was then subjected to a hydrothermal reaction at 150 °C for 12 h to obtain suspension B. The suspension B was centrifuged and vacuum freeze-dried to obtain precipitate A, i.e., 2D structured Mn(OH)2 hexagonal nanosheets;
[0043] (2) 1 g of Mn(OH)2 hexagonal nanosheets and 1 g of ruthenium trichloride were ultrasonically dispersed in 0.5 L of deionized water and stirred for 24 h for ion exchange reaction to obtain suspension C. Suspension C was centrifuged, washed, and dried to obtain precipitate B. Precipitate B was heated to 800 °C at a rate of 5 °C / min and reacted for 2 h to obtain Mn-doped RuO2 nanosheet catalyst, named 2D-Mn-RuO2-7. Example 8
[0044] (1) Under stirring, 10 mL of hydrazine hydrate solution (50 wt%) was added dropwise to 100 mL of 10 g / L potassium permanganate solution to obtain solution A, which was then subjected to a hydrothermal reaction at 150 °C for 12 h to obtain suspension B. The suspension B was centrifuged and vacuum freeze-dried to obtain precipitate A, i.e., 2D structured Mn(OH)2 hexagonal nanosheets;
[0045] (2) 1 g of Mn(OH)2 hexagonal nanosheets and 1 g of ruthenium trichloride were ultrasonically dispersed in 0.5 L of deionized water and stirred for 12 h for ion exchange reaction to obtain suspension C. Suspension C was centrifuged, washed, and dried to obtain precipitate B. Precipitate B was heated to 400 °C at a rate of 5 °C / min and reacted for 2 h to obtain Mn-doped RuO2 nanosheet catalyst, named 2D-Mn-RuO2-8. Example 9
[0046] (1) Under stirring, 10 mL of hydrazine hydrate solution (50 wt%) was added dropwise to 100 mL of 10 g / L potassium permanganate solution to obtain solution A, which was then subjected to a hydrothermal reaction at 150 °C for 12 h to obtain suspension B. The suspension B was centrifuged and vacuum freeze-dried to obtain precipitate A, i.e., 2D structured Mn(OH)2 hexagonal nanosheets;
[0047] (2) 1 g of Mn(OH)2 hexagonal nanosheets and 0.5 g of ruthenium trichloride were ultrasonically dispersed in 0.5 L of deionized water and stirred for 12 h for ion exchange reaction to obtain suspension C. The suspension C was centrifuged, washed, and dried to obtain precipitate B. The precipitate B was heated to 900 °C at a rate of 5 °C / min and reacted for 2 h to obtain Mn-doped RuO2 nanosheet catalyst, named 2D-Mn-RuO2-9. Comparative Example 1
[0048] (1) Dissolve 1 g of ruthenium trichloride raw material in 80 mL of deionized water and stir magnetically for 2 h to dissolve and mix, and adjust the pH of the system to 3 with 1 mol / L hydrochloric acid solution to obtain a ruthenium salt solution;
[0049] (2) under stirring conditions, 200 mL of a 30% by mass H2O2 solution as an oxidant was added dropwise to the ruthenium salt solution obtained in step (1), while increasing the stirring rate and continuing stirring, and heating the reaction at 80°C for 6 hours, the reaction system solution was transformed from dark brown to colorless, and a solution with a suspended black precipitate was obtained. The solution with the suspended black precipitate was aged for 2 hours and centrifuged to obtain a black precipitate. The black precipitate was washed with deionized water and then dried to obtain a black ruthenium dioxide solid;
[0050] (3) Grind the black ruthenium dioxide solid obtained in step 2, place it in a muffle furnace, and calcine it at 300°C for 12 hours to obtain a RuO2 catalyst.
[0051] Different from Example 1, Comparative Example 1 adopts the method provided in CN115818740A to prepare RuO2 catalyst. Comparative Example 2
[0052] (1) Under stirring, 10 mL of hydrazine hydrate solution (50 wt%) was added dropwise to 100 mL of 10 g / L potassium permanganate solution to obtain solution A, which was then subjected to a hydrothermal reaction at 150 °C for 12 h to obtain suspension B. The suspension B was centrifuged and dried at 60 °C to obtain precipitate A, i.e., 2D structured Mn(OH)2 hexagonal nanosheets;
[0053] (2) 1 g of Mn(OH)2 hexagonal nanosheets and 1 g of ruthenium trichloride were ultrasonically dispersed in 0.5 L of deionized water and stirred for 12 h for ion exchange reaction to obtain suspension C. Suspension C was centrifuged, washed, and dried to obtain precipitate B. Precipitate B was heated to 600 °C at a rate of 5 °C / min and reacted for 2 h to obtain Mn-doped RuO2 nanosheet catalyst, named 2D-Mn-RuO2.
[0054] The difference from Example 1 is that freeze drying is not used in step 1, but drying is performed at 60° C. Other conditions and step 2 remain unchanged. Comparative Example 3
[0055] (1) Under stirring, 10 mL of hydrazine hydrate solution (50 wt%) was added dropwise to 100 mL of 10 g / L potassium permanganate solution to obtain solution A, which was then subjected to a hydrothermal reaction at 150 °C for 12 h to obtain suspension B. The suspension B was centrifuged and vacuum freeze-dried to obtain precipitate A, i.e., 2D structured Mn(OH)2 hexagonal nanosheets;
[0056] (2) 1 g of Mn(OH)2 hexagonal nanosheets and 1 g of ruthenium trichloride were ultrasonically dispersed in 0.5 L of deionized water and stirred for 3 h for ion exchange reaction to obtain suspension C. The suspension C was centrifuged, washed, and dried to obtain precipitate B. The precipitate B was heated to 600 °C at a rate of 5 °C / min and reacted for 2 h to obtain a catalyst.
[0057] The difference from Example 1 is that the ion exchange time is shortened to 3 h in step 2. Other conditions in step 1 and step 2 remain unchanged. Comparative Example 4
[0058] (1) Under stirring, 10 mL of hydrazine hydrate solution (50 wt%) was added dropwise to 100 mL of 10 g / L potassium permanganate solution to obtain solution A, which was then subjected to a hydrothermal reaction at 150 °C for 12 h to obtain suspension B. The suspension B was centrifuged and vacuum freeze-dried to obtain precipitate A, i.e., 2D structured Mn(OH)2 hexagonal nanosheets;
[0059] (2) 1 g of Mn(OH)2 hexagonal nanosheets and 1 g of ruthenium trichloride were ultrasonically dispersed in 0.5 L of deionized water and stirred for 48 h for ion exchange reaction to obtain suspension C. The suspension C was centrifuged, washed, and dried to obtain precipitate B. The precipitate B was heated to 600 °C at a rate of 5 °C / min and reacted for 2 h to obtain a catalyst.
[0060] The difference from Example 1 is that the ion exchange time is extended to 48 hours in step 2. The other conditions of step 1 and step 2 remain unchanged.
[0061] Test Example 1
[0062] The 2D structured Mn(OH)2 hexagonal nanosheets prepared in Example 1 were tested by TEM. The results are as follows: Figure 2 As shown; TEM test was performed on the 2D-Mn-RuO2 prepared in Example 1, and the results are as follows Figure 3 The RuO2 catalyst prepared in Comparative Example 1 was characterized by scanning electron microscopy, and the results were as follows Figure 5 shown.
[0063] Depend on Figure 2 It can be seen that the prepared 2D structured Mn(OH)2 nanosheets have a typical hexagonal nanosheet structure with a size of about 300-500nm; after ion exchange reaction and high-temperature pyrolysis, Figure 3 The 2D-Mn-RuO2 material shown can still maintain a good hexagonal nanosheet structure, and its nanometer size is 300-500nm. Its smaller hexagonal nanometer size can avoid the collapse or accumulation of the sheet structure, thereby providing a larger specific surface area; and the smaller hexagonal nanometer size can fully expose the active sites of the noble metal Ru atoms, thereby improving the utilization rate of the noble metal Ru atoms in the catalytic process; and the 2D hexagonal nanosheet structure can provide a good contact interface between the active sites and the electrolyte, promoting the efficiency of electron / ion transmission, and unlike the Mn(OH)2 solid nanosheet, the interior of the 2D-Mn-RuO2 is significantly thinner, indicating the occurrence of ion exchange reaction; Figure 5 The figure shows RuO2 prepared by the traditional method. The results show that the overall size of the prepared RuO2 exceeds 1um, has an irregular shape, and is severely agglomerated, which seriously reduces the atomic utilization of the precious metal Ru.
[0064] The above results show that the ruthenium element is confined to the hexagonal nanosheet template through ion exchange reaction, and then calcined to obtain Mn-doped RuO2 nanosheet catalyst, which avoids the problem of easy agglomeration of Ru atoms in the traditional method of preparing RuO2 catalyst by direct high-temperature pyrolysis of metal ruthenium salt; and the unique hexagonal nanosheet structure has a large specific surface area, which can fully expose the active sites of the precious metal Ru atoms, thereby improving the utilization rate of the precious metal Ru atoms in the catalytic process, and the 2D hexagonal nanosheet structure can provide a good contact interface between the active sites and the electrolyte, promoting the efficiency of electron / ion transmission.
[0065] Test Example 2
[0066] The 2D-Mn-RuO2 prepared in Example 1 was subjected to XRD test, and the results were as follows: Figure 1 As shown, the catalyst prepared in Comparative Example 3 was subjected to XRD test, and the results are as follows Figure 7 As shown, the catalyst prepared in Comparative Example 4 was subjected to TEM test, and the results are as follows Figure 8 Shown
[0067] Figure 1 The XRD results show that the XRD peak of 2D-Mn-RuO2 corresponds to that of standard RuO2, indicating that 2D-Mn-RuO2 was successfully prepared, and no XRD peak of Mn oxide was found, indicating the successful doping of Mn element. The doping of Mn atoms can adjust the d-band center of the precious metal Ru atom, optimize the electronic structure of RuO2 catalyst and the adsorption / desorption ability of reaction intermediates on Ru sites, and solve the problem that the intrinsic activity of Ru is much lower than that of commercial Pt / C catalyst. Figure 7 The results showed that the characteristic peak of Mn2O3 appeared in the product, and the final product was a mixed product of Mn2O3 and RuO2, and it was impossible to prepare Mn-doped RuO2 catalyst. Figure 8 The results showed that after extending the reaction time to 48h, the long-term ion exchange caused it to decompose, and the structure of the prepared catalyst was a six-deformed nanoring with a hollow interior, which means that the prepared nanoring catalyst could not provide a large specific surface area.
[0068] The above results show that by controlling the ion exchange reaction time between 6-24h, the prepared Mn-doped RuO2 nanosheet catalyst can maintain the morphology characteristics of hexagonal nanosheets. This method is simple and easy to control, and can quickly and controllably prepare Mn-doped RuO2 nanosheet catalysts, providing an effective synthesis path for the large-scale development and utilization of ORR catalysts.
[0069] Test Example 3
[0070] The catalyst prepared in Comparative Example 2 was subjected to XRD test, and the results are as follows: Figure 6As shown in the figure, the characteristic peak of Mn2O3 appeared in the product, and the final product was a mixture of Mn2O3 and RuO2, and it was impossible to prepare Mn-doped RuO2 catalyst. This is because Mn(OH)2 was oxidized during the drying process, and the oxidized nanosheets could not undergo subsequent ion exchange reactions.
[0071] The above results show that vacuum freeze-drying is required in step 1 of the technical solution of the present invention.
[0072] Application Example 1
[0073] The 2D-Mn-RuO2 material prepared in Examples 1-9, the catalyst material prepared in Comparative Examples 1-4 and commercial Pt / C were used for the positive electrode ORR test of hydrogen-oxygen fuel cells in a 0.1M KOH alkaline environment, including the following application steps:
[0074] 10uL of 5mgmL -1 The catalyst slurry (5 mg of the prepared catalyst was dispersed in a mixed solution of 0.95 mL of isopropanol and 0.05 mL of Nafion by ultrasonication) was coated on a rotating disk electrode (electrode area: 0.196 cm 2 ) was used as the working electrode, the reference electrode and the counter electrode were reversible hydrogen electrode and graphite rod electrode respectively, and the electrochemical linear sweep voltammetry (LSV) test was carried out on a CHI760E electrochemical workstation in oxygen-saturated 0.1M KOH with the turntable speed adjusted to 1600 rpm;
[0075] Depend on Figure 4 It can be seen that the 2D-Mn-RuO2 catalyst material prepared in Example 1 of the present invention has a half-wave potential of 0.84V, and has ORR catalytic performance similar to that of commercial Pt / C. In addition, thanks to the optimization of the electronic structure of the RuO2 catalyst and the adsorption / desorption ability of the reaction intermediates on the Ru site by Mn atom doping, the performance of the 2D-Mn-RuO2 catalyst is greatly improved compared to RuO2 prepared by traditional methods.
[0076] Table 1 shows the ORR activity test data of Examples 1-9, Comparative Examples 1-4 and commercial Pt / C. It can be seen from Table 1 that the Mn-doped RuO2 catalyst prepared in Examples 1-9 has excellent catalytic activity, and its half-wave potential is 0.81-0.84V, showing ORR activity similar to that of the commercial Pt / C catalyst. Compared with the 2D-Mn-RuO2 prepared in Examples 1-9, the RuO2 catalyst prepared by the conventional method has a half-wave potential of only 0.58V, and its activity is relatively low. This indicates that the doping of Mn atoms is achieved through ion exchange and high-temperature pyrolysis, which can adjust the d-band center of the noble metal Ru atom, optimize the electronic structure of the RuO2 catalyst and the adsorption / desorption ability of the reaction intermediates at the Ru site, and solve the problem that the intrinsic activity of Ru is much lower than that of the commercial Pt / C catalyst.
[0077] The catalysts prepared by changing the reaction time in Comparative Examples 3 and 4 have half-wave potentials of 0.65 V and 0.71 V, respectively, and their activities are much lower than the 2D-Mn-RuO2 catalyst prepared in Example 1. This indicates that the unique hexagonal nanosheet structure can provide a larger specific surface area, which can fully expose the active sites of the precious metal Ru atoms, thereby improving the utilization rate of the precious metal Ru atoms in the catalytic process, and the 2D hexagonal nanosheet structure can provide a good contact interface between the active sites and the electrolyte, which plays a vital role in promoting the efficiency of electron / ion transmission.
[0078]
Claims
1. A method for preparing a Mn-doped RuO2 nanosheet catalyst, characterized in that: The following steps are involved: 1) Under stirring, hydrazine hydrate is added dropwise to a potassium permanganate aqueous solution to obtain solution A, and then a hydrothermal reaction is performed to obtain a suspension B. The suspension B is centrifuged and vacuum freeze-dried to obtain a precipitate A, i.e., 2D structured Mn(OH)2 hexagonal nanosheets; 2) Ultrasonic dispersion of 2D structured Mn(OH)2 hexagonal nanosheets and metal ruthenium salt in a solvent, stirring to produce an ion exchange reaction, to obtain a suspension C, centrifuging, washing, and drying the suspension C to obtain a precipitate B, and calcining the precipitate B to obtain a Mn-doped RuO2 nanosheet catalyst; The solvent is one of deionized water, methanol or ethanol; the metal ruthenium salt is one of ruthenium trichloride, ruthenium acetate or carbonyl ruthenium chloride; the ratio of 2D structure Mn(OH)2 hexagonal nanosheets, metal ruthenium salt and solvent is 1g:0.5-2g:0.5-1L; the ion exchange reaction time is 6-24h; the calcination process is to control the heating rate to be 2-10℃ / min, heat to 400-900℃, and keep warm for 2h.
2. The method for preparing the Mn-doped RuO2 nanosheet catalyst according to claim 1, characterized in that: In the step 1), the concentration of the potassium permanganate aqueous solution is 5-10 g / L, the mass ratio of potassium permanganate to hydrazine hydrate is 1:2.5-5; the hydrothermal reaction temperature is 150-200° C., the hydrothermal reaction time is 12 h; and vacuum freeze drying is used for drying.
3. An application of a Mn-doped RuO2 nanosheet catalyst prepared by the preparation method according to any one of claims 1 to 2, characterized in that: The Mn-doped RuO2 nanosheet catalyst is applied to the positive electrode of a fuel cell.
Citation Information
Patent Citations
Ruthenium dioxide nanometer cluster / carbon composite material and preparation method thereof
CN105006379A
Synthetic method of ruthenium dioxide nano-powder
CN115818740A
Preparation method of high-dispersion regular hexagonal layered manganese oxide nanosheet
CN103979609A
Preparation method of hexagonal amorphous MnOx and crystalline RuO2 heterostructure nano material
CN116103691A
Cited By
Transition metal anchored heteroatom doped RuO2 fiber aerogel electrocatalyst as well as preparation method and application thereof
CN120905702A